Aplikasi Sistem Pemesanan dan Penyewaan Sarana Olahraga (Sarola) Menggunakan Android - Dedy Apriyadi; Indra Maulana Yusup Kusumah; Heldan Muhammad Haidar (Jurnal Penelitian dan Pengembangan Teknologi Informasi dan Komunikasi, 2022)
The Sports Facility Application is one part of the long-distance sports facility booking and rental information system via internet technology media using the Android operating system. Booking and renting sports facilities carried out by most sports facility locations, one of which is the subject of the author's research, namely BCNY HOUSE, where activities related to booking and renting sports facilities are still carried out conventionally and it is difficult to obtain information in real time. The marketplace concept applied to the Sports Facility Application is expected to be a solution to the obstacles that exist in conventional sports facility booking and rental methods. This system aims to provide convenience to sports facility renters and sports facility owners, where this application will be a bridge between renters and owners of sports facilities and will be a container for various other sports facilities. This application offers various conveniences to obtain real-time information related to booking and renting sports facilities. The research was conducted using Qualitative methodology, with data collection research methods implemented at BCNY HOUSE and Software Development methods using the waterfall method (Classic Life Cycle). The model described by Roger S. Pressman (1992:24) has general steps including Analysis, Design, Implementation (Program Code Implementation), Testing and Deployment & Maintenance (Application & Maintenance). The implementation of this Sports Facility Application is made with facilities including sports facility management, field data management, facility information management, booking management, profile management, facility schedule management and report information management for admins.